2011 IEEE International Symposium on Electromagnetic Compatibility 2011
DOI: 10.1109/isemc.2011.6038323
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Power Balance Method to E field calculation in the ARIANE 5 launcher payloads cavities

Abstract: The present paper reports the main results of a study the aim of which being to apply the Power Balance Method to the electric field calculation in the ARIANE 5 launcher cavities of the Payloads section and in the launcher avionics bay. Indeed, the use of this simple method, based on the application of the Poynting's theorem and on the statistical properties of electrically large cavities stimulated by high frequency sources, is the most efficient one in terms of computation time and high frequency limit with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In spite of these evolutions, the over-sized complex cavities theory can still be applied. The study [1] showed that the absorption of the electric field by a material or an object is directly proportional to the apparent surface. For these frequencies, the skin depth is small enough that the absorption is located on the external layer.…”
Section: Resultantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of these evolutions, the over-sized complex cavities theory can still be applied. The study [1] showed that the absorption of the electric field by a material or an object is directly proportional to the apparent surface. For these frequencies, the skin depth is small enough that the absorption is located on the external layer.…”
Section: Resultantsmentioning
confidence: 99%
“…These conditions allow to obtain a homogenous and isotropic statistically field which can be defined by a Gaussian law according to two parameters: average power or average electric field and standard deviation which is the same for field's components. The validity of the method has already been verified for the upper part of Ariane 5 [1]. During this study, the lower bound of validity of the model has been verified but beyond 26 GHz the statistical distribution of the electric field seemed to move away from the theoretical law expected.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation